Pengaruh Substitusi Tepung Daun Kelor (Moringa Oleifera) terhadap Kadar Serat Pangan Total Produk Crackers - Afa Risda Ziana Putri; Sudrajah Warajati Kisnawaty; Pramudya Kurnia (Yayasan Literasi Sains Indonesia, 2026)
Nutritional issues in toddlers in Indonesia are still a focus, as evidenced by the high prevalence of malnutrition. The production of snack crackers made from Moringa oleifera leaf flour has the potential as an option to support fiber sufficiency and digestive system health in children. The present inquiry seeks to analyze the impact of Moringa leaf flour substitution on the content of total dietary fiber, water-soluble fiber, and water-insoluble fiber in cracker products. Experimental research involving four treatments of Moringa leaf flour substitution with two replications Fiber content analysis was executed using the enzymatic gravimetric method AOAC 991.43 standard and the data were subsequently analyzed using the One Way ANOVA test which was then followed by the Duncan Multiple Range Test (DMRT). There is an effect of Moringa leaf flour substitution on total dietary fiber, soluble fiber, and insoluble fiber with a p value of 0,000 (p <0.05). The content of total dietary fiber, water-soluble fiber, and water-insoluble fiber in treatment A (0%) was 4,18; 0,28; and 3,90 gr/100 gr, treatment B (10%) was 6,66; 0,50; and 6,17 gr/100 gr, treatment C (15%) was 8,21; 0,55; and 7,66 gr/100 gr, and treatment D (20%) was 10,14; 0,68; and 9,45 gr/100 gr. The 10%, 15%, and 20% formulations contain high fiber because they have more than 6 g of dietary fiber per 100 gr of product and can help meet children's daily fiber needs and support improving nutritional status in children with underweight.